1995
DOI: 10.1111/j.1432-1033.1995.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-peptide Sera Against Cell-CAM 105 Determine High Molecular-mass Variants of the Long Isoform in Rat Hepatocytes

Abstract: The glycoprotein cell-CAM 105 is a member of the carcinoembryonic-antigen-(CEA)-gene family, involved in cell-cell adhesion of rat hepatocytes and expressed on the cell surface as a long (L) and a short (S) isoform with slightly differing molecular masses and isoelectric points. The cDNA of the L-isoform has been isolated and sequenced, as confirmed by the preparation of specific anti-peptide sera [Lin, S.-H., Culic, O., Flanagan, D. & Hixson, D. C. (1991) Biochem. J. 278, 155-161]. Recently, two additional cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Using isoform-specific antibodies, we and others [39] have identified several high molecular mass, non-reducible, C-CAM1containing species in rat liver plasma membranes, indicating that C-CAM1 most likely interacts with a number of cellular proteins to form large complexes. This finding is of particular interest in view of the diverse functions attributed to this isoform [5,14,16], and suggests that through a variety of cellular interactions C-CAM may participate in or regulate a number of seemingly disparate cellular processes.…”
Section: Discussionmentioning
confidence: 68%
“…Using isoform-specific antibodies, we and others [39] have identified several high molecular mass, non-reducible, C-CAM1containing species in rat liver plasma membranes, indicating that C-CAM1 most likely interacts with a number of cellular proteins to form large complexes. This finding is of particular interest in view of the diverse functions attributed to this isoform [5,14,16], and suggests that through a variety of cellular interactions C-CAM may participate in or regulate a number of seemingly disparate cellular processes.…”
Section: Discussionmentioning
confidence: 68%
“…Fluorescence and electron microscopic analysis of cells labeled in suspension with these mAbs indicated that the reactive epitopes were located in the ectodomain of CEACAM1 a -4L. The preparation and characteristics of rabbit antisera against synthetic peptides corresponding to sequences unique to the cyto71 (pAb C3) and the cyto10 domain of CEACAM1 a -4L (pAb OB2) have been described previously by Lin et al (6) and Baum et al (38), respectively. mAb 324.5 recognizing a tumor-associated Ig-like membrane protein, TuAg.1 (39), was used as a negative control for the radioimmunoprecipitation analysis and adhesion blocking experiments.…”
Section: Methodsmentioning
confidence: 90%
“…Indirect Immunofluorescence Analysis-At 24 -48 h after transfection with Ceacam1 a -4L or Ceacam1 b -4S expression plasmids, COS-1 cultures growing in chamber slides were fixed in acetone and labeled by an indirect immunofluorescence protocol as described previously (36) with pAb 669, a polyclonal antibody recognizing both CEACAM1 a -4L and CEACAM1 b -4S (38), and mAb 5.4 (36) or mAb 362.50 (15). Liver tissue was harvested from adult male ACI or Fischer F344 rats (Harlan Sprague-Dawley, Indianapolis, IN) as described previously (14,15,36).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue transglutaminase, which can be activated by e.g. growth factor‐induced increase of the intracellular calcium concentration [18], is abundantly expressed in liver [10]and it is of particular interest that it is in this tissue that we [8]and others [9]have identified a number of high molecular weight C‐CAM‐L‐containing species. The abundance of a group of proteins with an apparent M r twice that of monomeric C‐CAM, coupled with our demonstration that C‐CAM is distributed as non‐covalently linked dimers within plasma membranes, led us to propose that a population of C‐CAM‐L dimers [8]may become covalently modified.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that C‐CAM is organised as non‐covalently linked dimers within the membranes of epithelial cells [8]. In addition, the detection of C‐CAM‐L‐containing species with apparent molecular masses twice that of monomeric C‐CAM, in extracts of rat liver plasma membranes [8, 9], led us to propose [8]that a population of C‐CAM‐L dimers may become covalently modified, perhaps by the action of tissue transglutaminase.…”
Section: Introductionmentioning
confidence: 99%